SEMIOTIKA ROLAND BARTHES DALAM SYAIR “ASYIQ MIN FALISTHIN” KARYA MAHMUD DARWISH - Moh Ali Wafi; Irfan Effendi (Fakultas Adab dan Humaniora UIN Raden Fatah, 2023)
This study aims to describe the meaning by using Roland Barthes' semiotic theory in Mahmud Darwish's poem entitled